IMPLEMENTASI KINERJA ROUTING DINAMIS PADA TOPOLOGI STAR DALAM MANAJEMEN JARINGAN LAN (LOCAL AREA NETWORK) DI PT. SUPER AIR JET - SUCIPTO, EKO ANGGA (PT Triputra Sejahtera Prima, 2023)
The use of computer networks in the current era of globalization is very rapid. This is widely marked by network users ranging from companies, government agencies, the private sector, to the world of Education. The research methodology that researchers use in this study uses two kinds of methods, namely data collection methods and system development methods. Analyze the performance of dynamic routing protocols in star topologies in the PT. Super Air Jet. Perform dynamic routing protocol performance testing based on delay, jitter, throughput and packet loss. The conclusions that can be drawn from this final project are as follows: Local area networks are built with Cisco Packet Tracer software, which when tried successfully connects via wireless networks. Testing whether the server-to-client or client-to-server connection has been successful. From the results of the implementation and analysis that have been explained, the author has several suggestions as follows: With direct implementation to hardware, you will get tangible results and may be easier in better design. Keywords: Network, dynamic routing, tes connection, Super Air Jet